The family in early Christianity. Lessons and impulses for today - Estévez López, Elisa (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2016)
The march of Christianity in the first four centuries testifies to how fathers and mothers were for their children the first preachers of the faith by word and example. This article focuses on the works that best reflect how the family was an area of growth and transmission of the faith. In these Christian documents we find exhortations and counsels about the contents, methods and purposes for education of the children. These testimonies are today relevant for a Christian education.
Keywords: Family; early Christianity; experience of faith; transmission of the faith; behaviour of believers.